Inhibition of complement activation, myeloperoxidase, NET formation and oxidant activity by PIC1 peptide variants. - Pamela S Hair; Adrianne I Enos; Neel K Krishna; Kenji M Cunnion (PLoS ONE)
Background A product of rational molecular design, PA-dPEG24 is the lead derivative of the PIC1 family of peptides with multiple functional abilities including classical complement pathway inhibition, myeloperoxidase inhibition, NET inhibition and antioxidant activity. PA-dPEG24 is composed of a sequence of 15 amino acid, IALILEPICCQERAA, and contains a monodisperse 24-mer PEGylated moiety at its C terminus to increase aqueous solubility. Here we explore a sarcosine substitution scan of the PA peptide to evaluate impacts on solubility in the absence of PEGylation and functional characteristics. Methods Sixteen sarcosine substitution variants were synthesized and evaluated for solubility in water. Aqueous soluble variants were then tested in standard complement, myeloperoxidase, NET formation and antioxidant capacity assays. Results Six sarcosine substitution variants were aqueous soluble without requiring PEGylation. Substitution with sarcosine of the isoleucine at position eight yielded a soluble peptide that surpassed the parent molecule for complement inhibition and myeloperoxidase inhibition. Substitution with sarcosine of the cysteine at position nine improved solubility, but did not otherwise change the functional characteristics compared with the parent compound. However, replacement of both vicinal cysteine residues at positions 9 and 10 with a single sarcosine residue reduced functional activity in most of the assays tested. Conclusions Several of the sarcosine PIC1 variant substitutions synthesized yielded improved solubility as well as a number of unanticipated structure-function findings that provide new insights. Several sarcosine substitution variants demonstrate increased potency over the parent peptide suggesting enhanced therapeutic potential for inflammatory disease processes involving complement, myeloperoxidase, NETs or oxidant stress.